Strategi Dakwah Kiai Muhammad Naf'an dalam Membentuk Akhlak Santri di Pondok Pesantren Al-Maimuniyyah Kudus - Serin Himatus Soraya; Mohammad Thoha Al Amin (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah, IAI Al-Qodiri Jember, 2022)
This study aims to describe the preaching strategy of Kiai Muhammad Naf'an in shaping the morals of students at the Al-Maimuniyyah Islamic Boarding School. This research is included in the type of qualitative research. The data collection method is carried out in three ways, namely interviews, observation and documentation. The data found were then analyzed descriptively qualitatively based on the Miles and Huberman analysis model, starting from the stages of data reduction, data presentation, and drawing conclusions. The results of the study found that Kiai Muhammad Naf'an in an effort to shape the morals of students at the Al-Maimuniyyah Islamic Boarding School implemented three da'wah strategies, namely 1) Sentimental Strategy, carried out by giving advice to students and teaching to love each other and prioritize togetherness among students. 2) Rational Strategy, carried out by holding recitation of moral books, enforcing rules, giving ta'zir or punishment, and conducting deliberation. 3) The sensory strategy is carried out by applying religious practices and examples.